Four novel Pleurocordyceps (Polycephalomycetaceae) species from China - Xiao, Yuan-Pin; Yang, Yu; Jayawardena, Ruvishika S.; Gentekaki, Eleni; Peng, Xing-Can; Luo, Zong-Long; Lu, Yong-Zhong (Frontiers in Microbiology, 2024)
Entomopathogenic fungi comprise an ecologically important group of specialized pathogens infecting other fungi, invertebrates and plants. These fungi are species-rich with a high diversity and broad distribution worldwide. The majority of entomopathogenic fungi belong to the clavicipitoids, which consist of the hypocrealean families Clavicipitaceae, Cordycipitaceae, Ophiocordycipitaceae and Polycephalomycetaceae. The latter is a newly established entomopathogenic family that was recently separated from Ophiocordycipitaceae to accommodate the genera Perennicordyceps, Pleurocordyceps and Polycephalomyces. In recent years, Polycephalomycetaceae has been enriched with parasitic and hyperparasitic fungi. With 16 species spread across China, Ecuador, Japan, and Thailand, Pleurocordyceps is the most speciose genus in the family. In this study, we expand the number of taxa in the genus by introducing four new Pleurocordyceps species from China P. clavisynnema, P. multisynnema, P. neoagarica, and P. sanduensis. We provide detailed descriptions and illustrations and infer genus-level phylogenies based on a combined 6-loci gene sequence dataset comprising internal transcribed spacer gene region (ITS), small subunit ribosomal RNA gene region (SSU), large subunit rRNA gene region (LSU), translation elongation factor 1-alpha gene region (TEF-1α), RNA polymerase II largest subunit gene region (RPB1) and RNA polymerase II second largest subunit (RPB2). This study contributes towards knowledge with regard to the diversity of Pleurocordyceps specifically and entomopathogenic Hypocreales more broadly.